The Influence of Capital Structure, Profitability and Company Size on Company Value at PT Kalbe Farma Tbk for the 2007-2022 Period - Aziziah, Aina (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2024)
This research aims to determine the influence of capital structure, profitability, and company size on company value (PBV) at PT Kalbe Farma Tbk for the 2007-2022 period. This research method uses quantitative methods that will be processed with the Eviews 12 SV application. The sample used is the financial report for the 2007-2022 period. Capital Structure shows a t-count value of -2.148 < t-table 2.145 and has a significance value of 0.0528 (0.0528 > 0 .05). Profitability (ROE) has a calculated t-value of 5.693 > t-table 2.145 and has a significance value of (0.0001 < 0.05). Company size (Total Assets) has a calculated t-value of 4.721 > t-table 2.145 and has a significance value of (0.0005 < 0.05). The results are influential and significant with a significance value of 0.000461 (0.000461 < 0.05) with a calculated f-value of 12.89326 > f-table 3.49 simultaneously.